Analysis of Factors Affecting Savings in Indonesia from 1990 to 2020 - Dientje Rumerung; Jani Effendy; Sherly F. Ferdinandus (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The objectives to be achieved in this study are: the impact of per capita income on the amount of savings in Indonesia; the influence of the Flower Tribes Rate (BI Rate) on the savings amount in Indonesia. And how per capita income, interest rates and inflation influence the amount of savings in Indonesia simultaneously. The data collected in this study is the time series data period from 1991 to 2020 as secondary data published by Bank Indonesia, Central Agency of Staitsitika. The analysis method used in this investigation is the Double Linear Regression Analysis Method which uses the IBM SPSS 25 program. The results obtained are that per capita income and inflation have a partial significant impact on public savings in Indonesia, while interest rates have no significant effect on public Savings. Inflation has contributed a huge drop in savings. If there is an increase in inflation, then it will have a huge impact on the ability of the people to save. Thus it may be suggested that efforts to control inflation should continue to preserve the purchasing power of the population and the ability of the people to save